1981
DOI: 10.1007/bf01324188
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and nuclear volume of human cells during the cell cycle

Abstract: The volumes of whole cells and nuclei of cultured human cells were studied at different times after synchronization of growth using the Coulter counter and scanning microphotometry. It was found that the increase in cell volume is compatible with both linear or exponential growth during the cell cycle. The growth of the nuclear volume is not correlated with the beginning of the DNA synthesis. The nuclear volume starts to increase already 6 hr prior DNA synthesis. The data also indicate that the nuclear volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…3 B and C). Because in Arabidopsis shoot apices G1, S, and G2, phases have been reported to last for ∼50%, ∼25%, and ∼15% of the cell cycle (42), our data imply that nuclei grow through each of these phases, as in other organisms (43,44). Following an asymmetrical division, the small daughter grew at a faster rate per unit size than the large daughter …”
Section: Discussionmentioning
confidence: 55%
“…3 B and C). Because in Arabidopsis shoot apices G1, S, and G2, phases have been reported to last for ∼50%, ∼25%, and ∼15% of the cell cycle (42), our data imply that nuclei grow through each of these phases, as in other organisms (43,44). Following an asymmetrical division, the small daughter grew at a faster rate per unit size than the large daughter …”
Section: Discussionmentioning
confidence: 55%
“…Nuclear cross sectional area is known to correlate with cell cycle stage (28). Comparing the nuclear areas of cells that formed foci after laser exposure (n ϭ 31, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear volume in metazoan cells can change without alterations in cellular DNA content. A handful of studies with mammalian cells have suggested, but not convincingly demonstrated, that the nucleus may increase in volume before S-phase (Maul et al, 1972;Yen and Pardee, 1979;Fidorra et al, 1981). It is evident in many animal embryos that nuclear volume shrinks during embryonic cleavage cycles as cell volume decreases (Wilson, 1925;Gerhart, 1980;Sulston et al, 1983).…”
Section: Discussionmentioning
confidence: 99%